Evaluation of an Internet‐based intervention for ICD patients with elevated symptoms of posttraumatic stress disorder. Issue 5 (19th March 2019) - Ford, Jessica; Littleton, Heather; Lutes, Lesley; Wuensch, Karl; Benton, Christie; Cahill, John; Hudson, Christopher; Nekkanti, Rajasekhar; Gehi, Anil; Sears, Samuel
Abstract: Background: To date, treatment to reduce posttraumatic stress disorder (PTSD) symptoms in implantable cardioverter defibrillator (ICD) patients has been limited by lack of symptom recognition, lack of provider referrals, barriers to treatment access, and inadequate evidence base of treatment effectiveness in this population. Methods: Participants were 46 patients with ICDs (17 paired) with elevated PTSD symptoms who were recruited in electrophysiology clinics at community and university hospitals as well as ICD support forums. Participants were provided the Web‐based, brief psychosocial intervention, which was tailored to ICD patients and contained elements of evidence‐based cognitive‐behavioral protocols for PTSD. Pretest and posttest measurement assessed participants' trauma experiences, mental health, and device‐specific distress (device acceptance and shock anxiety). Results: Postintervention scores on the PTSD Checklist (PCL; M = 35.5, SD = 10.09) were significantly lower than preintervention scores (M = 46.31, SD = 9.88), t (16) = 3.51, P = 0.003, d  = 1.08. Conclusions: Preliminary results indicate that future research with a more robust design is warranted. Given limitations in accessibility of mental health providers to manage cardiac‐related psychological sequelae, brief, Web‐based intervention may be an effective, supplemental, clinical modality to offer treatment to this population.